Comparison of two reference standards in validating two field mydriatic digital photography as a method of screening for diabetic retinopathy. - Scanlon, P; Malhotra, R; Greenwood, R; Aldington, S; Foy, C; Flatman, M; Downes, S (2003)
AIM: To compare two reference standards when evaluating a method of screening for referable diabetic retinopathy. METHOD: Clinics at Oxford and Norwich Hospitals were used in a two centre prospective study of 239 people with diabetes receiving an ophthalmologist's examination using slit lamp biomicroscopy, seven field 35 mm stereophotography and two field mydriatic digital photography. Patients were selected from those attending clinics when the ophthalmologist and ophthalmic photographer were able to attend. The main outcome measures were the detection of referable diabetic retinopathy as defined by the Gloucestershire adaptation of the European Working Party guidelines. RESULTS: In comparison with seven field stereophotography, the ophthalmologist's examination gave a sensitivity of 87.4% (confidence interval 83.5 to 91.5), a specificity of 94.9% (91.5 to 98.3), and a kappa statistic of 0.80. Two field mydriatic digital photography gave a sensitivity of 80.2% (75.2 to 85.2), specificity of 96.2% (93.2 to 99.2), and a kappa statistic of 0.73. In comparison with the ophthalmologist's examination, two field mydriatic digital photography gave a sensitivity of 82.8% (78.0 to 87.6), specificity of 92.9% (89.6 to 96.2), and a kappa statistic of 0.76. Seven field stereo gave a sensitivity of 96.4% (94.0 to 98.8), a specificity of 82.9% (77.4 to 88.4), and a kappa statistic of 0.80. 15.3% of seven field sets, 1.5% of the two field digital photographs, and none of the ophthalmologist's examinations were ungradeable. CONCLUSION: An ophthalmologist's examination compares favourably with seven field stereophotography, and two field digital photography performs well against both reference standards.